Enhanced wastewater treatment by modified basalt fiber bio-carriers: Effect of etching and surface functionalization. (1st April 2022) - Ni, Huicheng; Wang, Chencheng; Arslan, Muhammad; Qian, Junchao; Liang, Zhishui; Luo, Zhijun; Cai, Ruoqi; Gamal El-Din, Mohamed; Wu, Zhiren
Abstract: The application of biological carriers holds a central position in wastewater treatment for biofilm-mediated degradation processes. In this study, the surface of b asalt f ibers (BF) was m odified by combined e tching and g rouping (surface functionalization via attaching glutamic acid) to produce MBFEG . The etching modification enhanced the surface properties and specific surface area of BF. However, combined etching and functionalization resulted in the successful loading of amino acids on the surface of MBFEG, ultimately improving surface hydrophilicity, adsorption properties, and biophilicity of the bio-carrier. Three-dimensional confocal laser scanning microscopy confirmed that the combined modification was highly suitable in improving microbial activity and biophilicity. The microbial communities on MBFEG bio-carrier were rich and diverse indicating a stronger degree of biogeochemical cycling, indicating enrichment of nitrogen and carbon cycles. Conclusively, etching and grouping modification technology hold a promising future for BF application in biological wastewater treatment schemes. Graphical abstract: Image 1 Highlights: Effect of etching, surface functionalization, and synergistic modification was investigated. Synergistic modification (MBFEG ) enhanced surface characteristics for microbial adhesion. Bio-nest of MBFEG displayed higher bio-activity and wastewater treatment potential. Influence of environmental factors: hydrophilicity > biophilicity > adsorption capacity.